Proceedings of the 2019 International Conference on Organizational Innovation (ICOI 2019) 2019
DOI: 10.2991/icoi-19.2019.69
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of Leverage, Value Added and Size on Earning Management and Financial Performance of Indonesian Shariah Banking

Abstract: The main issues of researches about earnings management have been conducted extensively. Nowadays, the scope of research on earning management is extended to business fields based on Islamic finance. So this research objective is to determine the influence of value added, leverage and size on Shariah banking financial performance through earning management. Discretionary Accrual in Modified Jones Model is used in this research to measure earning management. Then, indicator Return On Asset is used in measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…This is reinforced by the observation of Laura and Cristina (2014); Uwalonma, Uwuigbe and Okorie (2015), that company size is a business attribute that gives a propensity to manage earnings, Leverage was found to have a significant and positive influence on conglomerate firms' earnings management in Nigeria. This positive association is in support of the research result of Shehu and Jubril (2012); Moussa, et al (2013); Irawati, Marlina & Sipayung (2019) that the higher leverage increases the possibility of earnings management. Furthermore, profitability has a positive relationship with earnings management which indicates that if current profit is high, managers would engage in the management of their earnings if they want their firms to survive amidst the worries of staying afloat with dwindling cash flow of the company as corroborated by Aziatul, et al (2015).…”
Section: Discussion Of Findingssupporting
confidence: 79%
“…This is reinforced by the observation of Laura and Cristina (2014); Uwalonma, Uwuigbe and Okorie (2015), that company size is a business attribute that gives a propensity to manage earnings, Leverage was found to have a significant and positive influence on conglomerate firms' earnings management in Nigeria. This positive association is in support of the research result of Shehu and Jubril (2012); Moussa, et al (2013); Irawati, Marlina & Sipayung (2019) that the higher leverage increases the possibility of earnings management. Furthermore, profitability has a positive relationship with earnings management which indicates that if current profit is high, managers would engage in the management of their earnings if they want their firms to survive amidst the worries of staying afloat with dwindling cash flow of the company as corroborated by Aziatul, et al (2015).…”
Section: Discussion Of Findingssupporting
confidence: 79%
“…Several previous studies found that leverage take positive effect and significant impact on earnings management as reported by (Wiyadi, Trisnawati, Sasongko, & Fauzi, 2015), (Alfina & Sambuaga, 2021), (Widyasmara, Andika, & Saputri, 2021), (Asim & Ismail, 2019), and (Irawati, Marlina, & Sipayung, 2019). Based on previous research, this study proposes the following hypothesis H1.…”
Section: The Effect Of Leverage On Corruption Fraud Proxied By Earnin...mentioning
confidence: 66%
“…Several previous studies found that leveragetake effectpositive and significant impact on earnings management as reported by [11,12,13,14,15].…”
Section: The Effect Of Leverage On Corruption Fraud Proxies Earning M...mentioning
confidence: 80%